2014
DOI: 10.1007/s10956-014-9527-3
|View full text |Cite
|
Sign up to set email alerts
|

Science Teachers’ Response to the Digital Education Revolution

Abstract: We report a case study of two highly qualified science teachers as they implemented laptop computers in their Years 9 and 10 science classes at the beginning of the 'Digital Education Revolution,' Australia's national oneto-one laptop program initiated in 2009. When a large-scale investment is made in a significant educational change, it is important to consider teachers perspectives and responses to such change and we draw from sociocultural perspectives for our analysis. Through interviews and classroom obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…A teacher is a key figure within the traditional concept of education. In contrast, some studies provide a rationale and positive experience of such changes (Bruce & Chiu, 2015;Instefjord, 2015;Nielsen et al, 2015;Tømte et al, 2015). Bruce and Chiu (2015) suggested that, to assign digital competence and promote the use of digital technologies within the framework of the professional didactic competency of teachers, it is necessary to integrate technology as a pedagogical tool for teachers more effectively and include it into teacher training programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A teacher is a key figure within the traditional concept of education. In contrast, some studies provide a rationale and positive experience of such changes (Bruce & Chiu, 2015;Instefjord, 2015;Nielsen et al, 2015;Tømte et al, 2015). Bruce and Chiu (2015) suggested that, to assign digital competence and promote the use of digital technologies within the framework of the professional didactic competency of teachers, it is necessary to integrate technology as a pedagogical tool for teachers more effectively and include it into teacher training programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is related to the constraints that exist in our education. The first obstacle is the challenge of teaching innovative science [3]. The second barrier is classroom and school connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth barrier is a change in classroom management. [3] The rest of this paper is organized as follow: Section II describes proposed research method. Section III presents the obtained results and following by discussion in section IV.…”
Section: Introductionmentioning
confidence: 99%
“…a commonly used term is classroom orchestration, which seems to highlight the complexity of teaching in today's digitized classroom. However, only a few studies from lower secondary school represent what seems to be the pervasive challenge across school levels and subjects: Classroom management in ICT environments requires (and may over time contribute to) a form of teacher resiliency that enables changes in pre-computer classroom strategies and pedagogy (Nielsen, Miller, & Hoban 2015), but teachers tend to stick to known and established teaching methods, despite being aware of the benefits of using ICT (Kretschmann 2015). Such a structure can contribute to a self-reinforcing spiral of preservation of old and familiar practices.…”
Section: Conceptual Frameworkmentioning
confidence: 99%